2009
DOI: 10.1021/jp810395j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monodispersed Co(Fe)/Carbon Nanocomposite Microspheres with Very High Saturation Magnetization

Abstract: Through the complexation of cyano groups in polyacrylonitrile (PAN) microspheres with cobalt (iron) ions under mild conditions, cobalt (iron)-containing PAN microspheres could be prepared effectively, then after pyrolyzation of the composite microspheres at 800 °C under N 2 atmosphere, Co(Fe)/carbon nanocomposite microspheres could be prepared, and the metal content is up to ∼71 wt % in the Co(Fe)/carbon nanocomposite microspheres. Thermogravimetric analysis, transmission electron microscopy, and vibrating sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…8,17,36 This suggests that only a small amount of cobalt oxides are present on the surfaces of the Fe 3 O 4 @C/Co composite, which are formed by air passivation. 32 Nevertheless, XRD analysis conrmed that cobalt in the Fe 3 O 4 @C/Co composites mainly presented as zero valence Co nanoparticles with a crystalline structure, and this is in accordance with the analysis in Section 3.1.…”
Section: Characterization Of the Compositessupporting
confidence: 86%
See 1 more Smart Citation
“…8,17,36 This suggests that only a small amount of cobalt oxides are present on the surfaces of the Fe 3 O 4 @C/Co composite, which are formed by air passivation. 32 Nevertheless, XRD analysis conrmed that cobalt in the Fe 3 O 4 @C/Co composites mainly presented as zero valence Co nanoparticles with a crystalline structure, and this is in accordance with the analysis in Section 3.1.…”
Section: Characterization Of the Compositessupporting
confidence: 86%
“…27 Chu et al entrapped Co 2+ (Fe 3+ ) into polyacrylonitrile (PAN) template microspheres, and pyrolysis of the template microspheres containing these metal complexes at 800 C for 1 h under a nitrogen atmosphere produced metal nanocrystals (Co 0 or Fe 0 ) embedded in the carbon microsphere. 32 Gong et al also prepared magnetic core/shell Co@C spheres using mixed plastics (consisting of polypropylene, polyethylene and polystyrene) as carbon source and it reduced Co 3 O 4 to Co 0 during the carbonization at 700 C under nitrogen atmosphere. 25 Shi et al found that the valence state of cobalt oxide and the reduction degree of graphene oxide (GO) of Co 3 O 4 /GO composites varied according to different calcination conditions.…”
Section: Preparation Of the Compositesmentioning
confidence: 99%
“…Monodisperse PAN-template microspheres were synthesized via soap-free emulsion polymerization as described previously [22]. In a typical synthesis, a solution of acrylonitrile (7.00 g), divinyl benzene (1.05 g), NaCl (0.004 g), and deionized water (133 mL) was charged into a flask, which was equipped with a mechanical stirring bar, a thermometer, and a condenser.…”
Section: Preparation Of Co(ii)/pan Microspheresmentioning
confidence: 99%
“…According to our previous study, cobalt nanoparticles have been embedded in the interior of the carbon microspheres, which protected the metal nanocrystals from oxidation, the CoNPs doped carbon microspheres possessed very high saturation magnetization [22].…”
Section: Introductionmentioning
confidence: 95%
“…Monodisperse microparticles and nanoparticles with uniform sizes and morphologies are used in bio-pharmaceuticals [ 1 , 2 ], drug delivery applications [ 3 , 4 ], electro/optic devices [ 5 , 6 ] and catalysis [ 7 , 8 , 9 ] because of their unique properties. Many efforts are made to produce uniform microparticles with custom sizes, shapes and morphologies using traditional methods, such as precipitation polymerization [ 10 , 11 ], emulsion polymerization [ 12 , 13 ], dispersion polymerization [ 14 , 15 ], SPG (Shirasu Porous Glass) membrane emulsification [ 16 , 17 ], and layer-by-layer assemblies [ 18 ]. However, these conventional emulsion droplet methods with bulk shearing forces are uncontrollable, and the resulting droplets, especially the non-spherical particles, are disparate in size and shape.…”
Section: Introductionmentioning
confidence: 99%